2014
DOI: 10.1016/j.conbuildmat.2014.04.139
|View full text |Cite
|
Sign up to set email alerts
|

Flexural creep of steel fiber reinforced concrete in the cracked state

Abstract: This is a repository copy of Flexural creep of steel fiber reinforced concrete in the cracked state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 5 publications
0
24
0
2
Order By: Relevance
“…Once all specimens were pre-cracked, they were transferred to the creep frames as seen in Figure 1 and tested under sustained flexural load for at least 90 days. A more detailed description of this creep test setup-up methodology is given in Arango et al 2012 andGarcía-Taengua et al 2014. Variables.…”
Section: Creep Test Methodologymentioning
confidence: 99%
“…Once all specimens were pre-cracked, they were transferred to the creep frames as seen in Figure 1 and tested under sustained flexural load for at least 90 days. A more detailed description of this creep test setup-up methodology is given in Arango et al 2012 andGarcía-Taengua et al 2014. Variables.…”
Section: Creep Test Methodologymentioning
confidence: 99%
“…Previous research on cracked steel FRC (Arango, 2010;Arango et al, 2012;García-Taengua et al, 2014) found low coefficients of creep at different long-term load levels for a 90 d period, but the type of fibre, the load level and the concrete strength significantly affected the creep behaviour. The authors concluded that the use of fibres, even at low contents, is a good strategy to control flexural creep in the cracked state.…”
Section: Introductionmentioning
confidence: 99%
“…A number of different factors affect creep of cracked FRC elements, relative to the composition and mechanical properties of the concrete matrix, fibres type and dosage, environmental conditions, loading conditions, or time, among other factors [3,4].…”
Section: Introductionmentioning
confidence: 99%